Managing Gastrointestinal Complications of Diabetes - Sellin, Joseph (Springer International Publishing : Imprint: Adis, 2017)
An ideal clinical handbook for medical professionals that regularly treat patients with diabetes and comorbid gastrointestinal complications. The concise format provides evidence-based content with a targeted emphasis on diagnosis, as up to 75% of patients visiting diabetes clinics report significant gastrointestinal symptoms. Includes guidelines for complication prevention, treatment, and long-term disease management.
Keywords: Medicine.; General practice (Medicine).; Diabetes.; Endocrinology.; Gastroenterology.; Primary care (Medicine).; elektronické knihy; electronic books